Respon Pertumbuhan Vegetatif Bibit Kelapa Sawit (Elaeis quineensis Jacq) Dengan Pemberian Abu Janjang Kosong dan Biochar Sekam Padi Dengan Komposisi Berbeda Pada Media Tanah di Fase Prenursery - Buhri Andika Siahaan; Sumihar Hutapea; Rizal Aziz (Jurnal Ilmiah Pertanian ( JIPERTA), 2022)
Lack of availability of soil nutrients to excessive leaching and erosion, this makes it difficult to get soil media. It is alternative as nutrients replasment such as empty bunch ash and rice husk biochar. This study aims to determine the response of  vegetative growth of oil palm seedlings with the provision of empty bunch ash and rice husk biochar in the prenursery. The design used in this study was a factorial randomized block design (RAK) consisting  2 (two) treatment factors, namely : 1) empty bunch ash dose factors (A) which consists of 4 levels, namely: A0= control (without empty bunch ash), A1= empty bunch ash 250 gr/polybag 2 kg, A2= empty bunch ash 500 gr/polybag 2 kg, A3= empty bunch ash 750 gr/polybag 2 kg. 2) dose factor of rice husk biochar (B) concisting of 4 levels, namely: B0= control (without rice husk biochar), B1= rice husk biochar 5 tons/ha (0.5 kg/plot) or 100 gr/polybag 2 kg, B2= rice husk biochar 10 tons/ha (1 kg/plot) or 200 gr/polybag 2 kg, B3= rice husk biochar 15 tons/ha (1.5 kg/plot) or 250 gr/polybag 2 kg. The result showed that the empty bunch ash treatment had a significant effect on plant height, stem diameter, leaf area and number of leaves, the A1 treatment with 250 gr/polybag (25%) was the best treatment had a significant effect, B3 treatment by giving 250 gr/polybag (1,5 kg/plot) was the best treatment to be applied to prenursery oil palm seedlings.